Sejarah bangsa Israel dalam bibel dan Al-quran : Sebuah Penelitian Islamic Archaeology / Louay Fatoohi, Shetha Al-Dargazelli; penerjemah, Munir A. Muin; penyunting, Andityas Prabantoro - FATOOHI, Louay; Al-Dorgazelli, Shetha; Muin, Munir A; Prabantoro, Andityas (Mizania, 2007)
360 hlm. ; 24 cm